The effect of modification “throwing-catching ball” in manipulative skill intellectual disability children - Septaliza, Dewi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
The purpose of the research is to know the effect on the modification of “throwing-catching ball” in manipulative skill intellectual disability children. This study used quasi-experimental with a pretest-posttest design. Based on sampling technique with purposive sampling, this research used 10 samples. This research used the throwing-catching the ball instrument test. After analyzing data, value of the pretest was obtained with an average value of 3,8, minimum data 1, maximum data 6, and with a range of 5. Meanwhile of the posttest was obtained an average value of 10, minimum data 6, maximum data 2, and with range 6. Based on the results of t test showed 0,005 < 0,05. Meaning that there is an effect on the modification of “throwing-catching ball” in manipulative skill intellectual disability children. Hopefully, this research can be used as a basis for the next research, by paying attention on characteristics of intellectual disability children who require special assistance and learning and be more creative in developing game models to improve the manipulative skill on intellectual disability children.